One-step in situ calcination synthesis of g-C3N4/N-TiO2 hybrids with enhanced photoactivity. Issue 16 (1st February 2016) - Sun, Shanfu; Sun, Mingxuan; Fang, Yalin; Wang, Ying; Wang, Huiping
Abstract : A series of g-C3 N4 /N-TiO2 composites were prepared by a solid-phase calcining process and their enhanced visible light photoresponse, photocatalytic activity, and photoelectrochemical performance were demonstrated. Abstract : A series of composites, based on graphitic carbon nitride and nitrogen-doped titanium dioxide (g-C3 N4 /N-TiO2 ), were prepared by a solid-phase calcination process, in which a homogenous mixture containing melamine and TiN was calcined at 550 °C for 3 h in air. Various techniques such as X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS), and UV-vis diffuse reflectance spectroscopy (UV-vis DRS) characterized the as-prepared composites. The results suggested that nitrogen was incorporated into the TiO2 lattice that formed the N–Ti bonds, which was followed by the successful combination of g-C3 N4 with N-TiO2 . A red-shift of absorption edge in the light region and more absorption in the visible light region were observed for the prepared composites. The synthesized composites exhibited excellent photocatalytic activities, which were evaluated by the degradation of methylene blue (MB) after irradiation with visible light. Especially, g-C3 N4 /N-TiO2 composites, prepared using melamine and TiN with a mass ratio of 1 : 1, showed the highest photocatalytic activity, and the corresponding rate of MB degradation was 0.028 min −1, which was 1.9 times greater than that of N-TiO2 (0.015 min −1 ). Furthermore, the photoelectrochemical performances of the samples on illumination with UV-visible light were evaluated. Remarkable enhancement of photoelectrochemical response of g-C3 N4 /N-TiO2 composites in UV-visible light, compared to pristine N-TiO2, was noticed. The co-modifications of TiO2 with N doping and g-C3 N4 coupling resulted in an enhancement in the capacity of light absorption and an improvement in the transfer of charge carriers, which predominantly contributed to the improvement of photoactivity. This study develops a new and facile fabrication procedure for g-C3 N4 /N-TiO2 hybrids and represents an important step in the improvement of solar energy conversion using cost-effective materials.